Engineering electrocatalyst for low-temperature N2 reduction to ammonia. (April 2021) - Rehman, Faisal; Delowar Hossain, Md; Tyagi, Abhishek; Lu, Dong; Yuan, Bin; Luo, Zhengtang
Graphical abstract: Abstract: Ammonia (NH3 ) is a significant energy source, in addition to its conventional uses for inorganic fertilizers, explosives, dyes, and resins. Recently, there has been tremendous interest towards electrochemical NH3 synthesis via nitrogen reduction reaction (NRR) under ambient conditions, to substitute the conventional Haber-Bosch process. In this review, the fundamentals and mechanism for electrochemical nitrogen fixation are summarized. The NRR performances for all the important electrocatalysts with a special focus on two-dimensional (2D) materials, and theoretical insights from recent literature are comprehensively summarized. Among them, 2D materials are especially promising due to the versatile tools that can be leveraged for the structure design. Based on these studies, guidelines for achieving high selectivity and high NRR catalytic activity are provided. Strategies for the catalyst design, cell configuration, and electrolyte choices to tackle several challenges related to NRR are delineated in a holistic way. Furthermore, important aspect of environmental contamination effect is also discussed. This review provides direction for electrochemical catalyst engineering and guidance for experimental practices to explore the realm of electrochemical nitrogen reduction reaction.